Research of rotating and ultrasonic cycling fatigue in high-cycle regimes - LIU Lu; WANG Shengnan; MA Yifan (Journal of Aeronautical Materials, 2024)
The effects of stress ratio（R），loading condition，and MnS inclusion on the fatigue behavior of medium-carbon pearlitic high strength steel were investigated by the combination of rotating（frequency of 52.5 Hz，103-108）bending and ultrasonic （frequency of 20 kHz，5×104-109）axial cycling tests in high-cycle and very-high-cycle regimes. The study results show that all the S-N curves present horizontal asymptotic shapes and have clear fatigue limits. The fatigue limits（260-270 MPa）for R = −1 obtained by ultrasonic test are 140-150 MPa，which are lower than that（400-410 MPa）obtained by rotating bending，and the limit values for R = 0.3 are in the range of 195-205 MPa. For rotating bending，the fatigue fractures are originated from the surface matrix of the specimen，whereas for ultrasonic fatigue，both surface and interior crack initiation occur，and cracks are all initiated from MnS inclusions regardless of stress ratios. The influence of MnS inclusions on crack initiation and propagation is studied by finite element method. The side of elliptical MnS inclusions has higher stress concentration than the tip position，which leads to crack initiation from the side of inclusions.